Studies on Amanita (Basidiomycetes: Amanitaceae) in Northern Thailand - Sanmee R. (2014)
Specimens of the genus Amanita, collected from northern Thailand and deposited in the fungal herbarium of Chiang Mai University and some overseas herbaria were studied. Twenty-five taxa, including eighteen new to Thailand, are described briefly. A key to species is provided. The new records for Thailand are A. alboflavescens, A. avellaneosquamosa, A. chepangiana, A. clarisquamosa, A. flavipes sensu lato, A. fritillaria, A. fuliginea, A. hongoi, A. japonica, A. manginiana sensu W.F. Chiu, A. obsita, A. ovalispora, A. pseudoporphyria, A. rubrovolvata, A. sinensis, A. sinocitrina, A. subglobosa, and A. virgineoides. A type study of A. pudibunda is included. Amanita frostiana sensu R. Heim is proposed to be properly diagnosed as A. rubrovolvata.